Advances in COVID-19 Vaccines and New Coronavirus Variants - Liu, Mengchen; Li, Yunqiao (Frontiers in Medicine, 2022)
With the successful development of the COVID-19 vaccines and increased vaccination coverage, great progress in global outbreak control has been made in several countries. However, new coronavirus variants emerge and continue to spread rapidly, causing a new wave of economic and social upheaval worldwide. The spread of new coronavirus variants poses a new and enormous challenge to vaccination and pandemic control, so further studies to explore and develop vaccines for the prevention and control virus infection are warranted. In this review, we provide an overview of the most prevalent variant strains including Omicron, and explore the effectiveness of COVID-19 vaccines against related variant strains to better understand existing vaccines and to facilitate improved research into new vaccines. In addition, this review discusses existing strategies to increase vaccine efficacy and introduces novel vaccines by the non-injection route.